THE RELATIONSHIP BETWEEN NURSE-PATIENT COMMUNICATION AND MEDICATION ADHERENCE IN SAUDI ARABIAN PRIMARY HEALTHCARE CENTERS - Wajed Salem Alanezi, Wassala Salem Alanazi, Saadaha Sowied Alanzi, Nourah Jalawi Alshammari, Tahani Sanad Farhan Aldaferiy, Dhahyah Nemer Al Shammari, Saitah Mohammad Alsuhali, Dalail Bataha Aqieial Aldhafeeri, (Chelonian Research Foundation, 2022)
Effective nurse-patient communication is crucial for promoting medication adherence, particularly in primary healthcare settings. This study aimed to investigate the relationship between nurse-patient communication and medication adherence among patients in Saudi Arabian primary healthcare centers. A cross-sectional survey was conducted with a sample of 400 patients from eight primary healthcare centers in Riyadh, Saudi Arabia. The Nurse-Patient Communication Scale (NPCS) and the Medication Adherence Questionnaire (MAQ) were used to measure nurse-patient communication and medication adherence, respectively. Descriptive statistics, Pearson's correlation, and multiple linear regression analyses were performed to examine the relationship between nurse-patient communication and medication adherence, while controlling for demographic variables. The results showed a significant positive correlation between nurse-patient communication and medication adherence (r = 0.679, p < 0.001). Multiple linear regression analysis revealed that nurse-patient communication was a significant predictor of medication adherence (β = 0.638, p < 0.001), after controlling for age, gender, education level, and chronic disease status. The findings highlight the importance of effective nurse-patient communication in promoting medication adherence and suggest that interventions aimed at improving communication skills among primary healthcare nurses may lead to better patient outcomes. Recommendations for practice and future research are discussed. Keywords: nurse-patient communication, medication adherence, primary healthcare, Saudi Arabia, cross-sectional survey